Pengaruh Profitabilitas, Leverage, Firm Size, dan Net Working Capital Terhadap Cash Holding - William Romel; Agustin Ekadjaja (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2023)
The goals of this research is to obtain empirical evidence regarding the effects of profitability, leverage, firm size, and net working capital on cash holding in consumer non-cyclical sector companies listed on the Indonesia Stock Exchange (IDX) for the 2019 – 2021 period. Purposive sampling was used in this study to select 62 samples and 186 data points from consumer non-cyclical companies. Data for this study were collected and analysed using Microsoft Excel 2016 and Eviews 12. The result of this research indicates that profitability and firm size have no effects on cash holding. Meanwhile, leverage and net working capital have a significant negative effect on cash holding.